Penerapan Metode Modeling Berbantuan Media Gambar untuk Meningkatkan Keterampilan Membaca Puisi Siswa Kelas IV SDN Tampirkulon 2 Kecamatan Candimulyo Kabupaten Magelang - Fatikasari, Addina Nasihah; Purnanto, Arif Wiyat; Pradana, Agrissto Bintang Aji (Universitas Muhammadiyah Magelang, 2022)
This study aims to determine the implementation of image assisted modeling method to improve poetry reading skills of fourth grade students at SDN Tampirkulon 2, Candimulyo Sub-District, Magelang Regency. The research was Classroom Action Research (CAR). The subjects of this study were fourth grade students of SDN Tampirkulon 2, Candimulyo District, Magelang Regency, consisting of 3 students. This research used the research design of Prof. Suharsimi Arikunto. Methods of data collection were observation and performance test. The data analysis method used was qualitative and descriptive quantitative analysis. The results showed that the implementation of image assisted modeling method is able to improve poetry reading skills of fourth grade students at SDN Tampirkulon 2, Candimulyo Sub-District, Magelang Regency. It can be seen from the improved results of each cycle which and the achievement of indicators of success. In the first cycle, the percentage of classical completeness was 33% or 1 out of 3 students completed with an average value of 70.8. While in the second cycle there was an increase in the students' poetry reading performance score, in which 67% or 2 out of 3 students completed with an average score of 79.2.